Investigation of cleat and micro-fracture and its aperture distribution in the coals of different ranks in North China: Relative to reservoir permeability - Huang, Qiang; Du, Zhigang; Liu, Hewu; Niu, Qinghe; Fang, Huihuang; Yang, Jinyang; Lou, Minghang (Frontiers in Earth Science, 2023)
The aperture of cleat and micro-fracture in coal plays an important role in the permeability of the coal bed. In this paper, optical microscopy and scanning electron microscopy were taken to investigate the cleat and micro-fracture morphology and its aperture, distribution of minerals, and matrix/fracture interactions. The mineralized and unmineralized cleats suggest that there are multi-stage evolution processes for cleat formation during the coalification process. The micro-fracture distribution of coals is closely related to their components including the organic macerals and inorganic minerals. It is prone to develop at the junction surface of organic macerals or the surface of organic and inorganic minerals. The mineral-genetic related micro-fracture formation mechanism can be classified as intra-crystal micro-scale fracture, extra-crystal micro-scale fracture, and grain edge micro-scale fracture. Compared with the low- and high-rank coals, the cleat and micro-scale fracture in high-rank coal are usually filled with carbonate minerals and clay minerals. Statistical analysis reveals that the aperture distribution of cleat and micro-fracture in coal meets the log-normal distribution. The aperture of cleat and microfracture shows a decreasing trend with the increase of coal rank. Generally, due to the differential aperture size, the cleat contributes more to the permeability than the micro-fracture for the low-rank coal. For the middle- and high-rank coals, the contribution of cleat and micro-fracture to the coal permeability will be close. With the increase of coal rank, the role of cleat contributing to the reservoir permeability decreases, whereas the role of micro-fracture contributing to the reservoir permeability increases. The possible reasons for the extremely low reservoir permeability in China may be that : (1) the subsurface cleat and micro-fracture close their apertures significantly due to the larger geo-stress; (2) the cleat and micro-fracture have better permeability in the geological history, which help the precipitation of minerals to decrease the coal reservoir permeability. It suggests that the acid solvent (e.g., HAc, HCl, and HF) added to the drilling or hydraulic fracturing fluid and the geo-stress relief technologies may be an effective way to enlarge the cleat or micro-fracture aperture and then enhance the reservoir permeability for CBM exploitation.